Observed multivariable signals of late 20th and early 21st century volcanic activity. Issue 2 (20th January 2015) - Santer, Benjamin D.; Solomon, Susan; Bonfils, Céline; Zelinka, Mark D.; Painter, Jeffrey F.; Beltran, Francisco; Fyfe, John C.; Johannesson, Gardar; Mears, Carl; Ridley, David A.; Vernier, Jean‐Paul; Wentz, Frank J.
Abstract: The relatively muted warming of the surface and lower troposphere since 1998 has attracted considerable attention. One contributory factor to this "warming hiatus" is an increase in volcanically induced cooling over the early 21st century. Here we identify the signals of late 20th and early 21st century volcanic activity in multiple observed climate variables. Volcanic signals are statistically discernible in spatial averages of tropical and near‐global SST, tropospheric temperature, net clear‐sky short‐wave radiation, and atmospheric water vapor. Signals of late 20th and early 21st century volcanic eruptions are also detectable in near‐global averages of rainfall. In tropical average rainfall, however, only a Pinatubo‐caused drying signal is identifiable. Successful volcanic signal detection is critically dependent on removal of variability induced by the El Niño–Southern Oscillation. Key Points: Detection of multivariable signals of recent volcanic activity in observations Volcanic signals are identifiable in both the late 20th and early 21st centuries Successful volcanic signal detection depends on removal of ENSO variability